PELAKSANAAN KEGIATAN EKTRAKURIKULER DI SLB AL-ISHLAAH PADANG - Armayanti - - (Jurnal Penelitian Pendidikan Khusus, 2014)
This research is motivated by the implementation of Extracurricular Activities in SLB AL-Ishlaah Padang. The study aimed to determine the types of Extracurricular Activities, how to program, barriers experienced, and schools in an effort to overcome the problems encountered. This research method qualitative shape description, Data was collected by interview, observation, and documentation. Data analysis was performed during the study.